2005
DOI: 10.1079/asc42040357
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cereal type and exogenous enzyme supplementation in pig diets on nutrient digestibility, intestinal microflora, volatile fatty acid concentration and manure ammonia emissions from finisher pigs

Abstract: A 2 × 2 factorial experiment was conducted to investigate the interaction between cereal type (wheatv. barley) and an exogenous enzyme supplement (with or without) on nutrient digestibility, large intestinal microflora, volatile fatty acid profile andin vitromanure ammonia emissions from finisher pigs. The enzyme supplement used contained endo-1, 3-β-glucanase (EC 3·2·1·6) and endo-1, 4-β-xylanase (EC 3·2·1·8). The diets were formulated to contain similar concentrations of net energy (9·8 MJ/kg) and lysine (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 23 publications
5
90
2
Order By: Relevance
“…The improved growth performance of growing pigs fed diet supplemented with β-mannanase found in these trials might be partly due to enhanced digestibility of DM, GE and β-mannan, which was in agreement with Kim et al (2013) who reported higher final BW, digestibility of DM and GE in β-mannanase supplemented diet. High levels of NSP in pig diets can cause an increase in digesta viscosity, preventing interaction between substrate and digestive enzymes and, hence, reducing the nutrient digestibility (O'Connell et al, 2005;Passos et al, 2015). Previous studies demonstrated that supplementation of exogenous enzymes to high-NSP diets reduced the viscosity of digesta and enhanced the nutrient utilization (Parkkonen et al, 1997;Grandhi, 2001;Ji et al, 2008;Tapingkae et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The improved growth performance of growing pigs fed diet supplemented with β-mannanase found in these trials might be partly due to enhanced digestibility of DM, GE and β-mannan, which was in agreement with Kim et al (2013) who reported higher final BW, digestibility of DM and GE in β-mannanase supplemented diet. High levels of NSP in pig diets can cause an increase in digesta viscosity, preventing interaction between substrate and digestive enzymes and, hence, reducing the nutrient digestibility (O'Connell et al, 2005;Passos et al, 2015). Previous studies demonstrated that supplementation of exogenous enzymes to high-NSP diets reduced the viscosity of digesta and enhanced the nutrient utilization (Parkkonen et al, 1997;Grandhi, 2001;Ji et al, 2008;Tapingkae et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Manure pH is determined by the level of urea hydrolysis, total ammoniacal nitrogen, the dietary electrolyte balance (dEB) and by the VFA concentration of the excreta (Canh et al, 1998b). Only a minor reduction in pH is required to reduce ammonia emissions (O'Connell et al, 2005). At a low pH, ammonia remains stable in the slurry as ammonium.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, there are a number of factors that drive the volatilisation of NH 3 such as the equilibrium of ammonia with ammonium, pH, temperature and ammonia concentration (McCrory and Hobbs, 2001). The pH of slurry is of huge relevance to ammonia emissions from pig manure (Sommer and Husted, 1995;O'Connell et al, 2005), with just a minor change having a substantial effect (Canh et al, 1998a). Secondly, there may not have been enough inulin present to bring about a reduction in manure pH and manure ammonia emissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of these polysaccharides, in particular the soluble fraction, can cause an increase in digesta viscosity, preventing interaction between nutrients and digestive enzymes (Campbell and Bedford, 1992) and reducing nutrient digestibility (O'Connell et al, 2005). The addition of enzyme preparations can effectively degrade viscous non-starch polysaccharides (NSP) of the diet leading to a reduction in the viscosity of the diet and in enhanced nutrient utilisation (Dierick and Decuypere, 1996).…”
Section: Introductionmentioning
confidence: 99%